Comparative Analysis of Comfort Temperature of School Children and Their Teachers - Munonye, Charles; Ngobili, Michael; Umeora, Chukwunonso; Oluchi, Ifebi; Maduka, Nkechi; Onwuzuligbo, Chijioke (Research & Development, 2023)
Thermal comfort in learning environments influences the student’s focus and learning productivity. This study aims to evaluate and compare the adaptive thermal comfort of schoolchildren and their teachers in naturally ventilated primary schools in some selected cities in Imo State Nigeria. To achieve these objectives, the study analyzed the data collected from 330 pupils and 44 teachers in six surveyed classrooms in two types of classroom buildings. The recorded data in the surveyed classrooms consisted of four environmental factors and two personal factors. At the same time, the subjects filled out the questionnaires asking them about thermal sensation and thermal preferences against the classrooms’ thermal requirements. The results of the measurements showed that the indoor mean air temperature, relative humidity, and air velocity were 29.1°C, 71.2%, and 0.19m/s, respectively. The mean thermal sensation votes of the children were +0.16 while that of their teachers was +0.58. The preferred temperatures were 27.4°C and 29.4°C for the schoolchildren and the teachers, respectively. Furthermore, the comfort range of the students was between 25.8°C - 31.6°C, and that of the teachers was between 28.0°C - 29.9°C. Based on the results of this study conducted in primary school buildings located in warm and humid climates, the thermal comfort perception of children and adults differ. This information will serve as a guide to professionals in the built environment, especially architects when designing primary school buildings in the warm and humid climates.
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:keyword:comfort temperature; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; openalex:n:1; openalex:yes